2021
DOI: 10.1111/mpp.13102
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations in nitric oxide homeostasis promote Arabidopsis disease susceptibility towards Phytophthora parasitica

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Cui B, et al [2] reported that the level of NO is significant for setting up basal resistance against Phytophthora parasitica in Arabidopsis. Moreover, transformations in S-nitrosoglutathione Reductase 1 (GSNOR1) impair both SA and Reactive Oxygen Species (ROS) amassing, driving to improved helplessness towards P. parasitica.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cui B, et al [2] reported that the level of NO is significant for setting up basal resistance against Phytophthora parasitica in Arabidopsis. Moreover, transformations in S-nitrosoglutathione Reductase 1 (GSNOR1) impair both SA and Reactive Oxygen Species (ROS) amassing, driving to improved helplessness towards P. parasitica.…”
Section: Introductionmentioning
confidence: 99%
“…Later thinks about have moreover uncovered a part for NO as a signaling atom in plants. As a formative controller, NO advances germination, leaf expansion and root development, and delays leaf senescence and natural product development [2].…”
Section: Introductionmentioning
confidence: 99%
“…SA modulates the biosynthesis of auxin/JA and antagonizes their signaling in pathogenesis responses (Vlot et al., 2009). SA also mediates NO synthesis to regulate stomatal conductance by integrating into the Ca 2+ /CPK‐dependent ABA signaling pathway (Cui et al., 2021; Prodhan et al., 2018; Zottini et al., 2007). In addition, it is required for optimal photosynthesis and redox homeostasis (Mateo et al., 2006).…”
Section: Introductionmentioning
confidence: 99%